Dosa Dalam Perspektif Biblis Dan Implikasi Pastoralnya - Silvester Manca (STIPAS St. Sirilus Ruteng, 2017)
The Holly Bible provides a very complete view of the theme of sin. Scripture views sin as a matter of human relation with God and fellow creatures, not primarily as a violation of the law. Sin is also understood as a double-faced reality because sin corrupts the human relationship not only with God but also with others. Even sin destroys human existence and dignity. Moreover, Scripture never speaks of sin separately from the theological idea of God’s goodness and mercy. Thus, sin does not at all undo God’s plan to save man and the universe.